Relationship Between Temporal Pattern Perception Test and Mismatch Negativity in Children With Auditory Processing Disorder and Dyslexia - Mohideen, Roshan Shahinas Peer Mohammed; Thangaraj, MuthuSelvi (Journal of audiology & otology, 2023)
Background and Objectives: Mismatch negativity (MMN) is an objective test for assessing auditory function. The central auditory nervous system processes different stimuli in various ways. This can be assessed using MMN elicited with different stimuli in an “oddball” paradigm. This study evaluated temporal ordering skills using MMN with different durations of stimuli. This study aimed to determine the correlation between the results of the behavioral duration pattern test (DPT) with MMN in typically developing children versus children with dyslexia and auditory processing disorder (APD). Subjects and Methods: Two groups of children participated in the study. The experimental group included 16 children with APD and dyslexia who had scored below the age-matched scores in the DPT. The control group consisted of 16 typically developing children with age-matched scores in the DPT. MMN was elicited using the same stimuli (250 ms and 500 ms) as that of the DPT in both groups. MMN latency, MMN amplitude, and area under the curve were measured in both groups. Results: Compared to the control group, children with APD and dyslexia showed increased MMN latency, reduced amplitude, and decreased area under the curve. There was a low correlation (r= -0.293, p<0.05) between MMN latency and DPT scores. The correlation between MMN amplitude and DPT scores was moderate (0.472, p<0.001). Furthermore, a strong correlation (0.536, p<0.001) between area under the curve and DPT scores was demonstrated. Conclusions: MMN amplitude and MMN area under the curve could serve as valid indicators during assessment of temporal ordering in children with APD and dyslexia.